Enhancement of Dissolution Rate and Bioavailability of Aceclofenac Through Complexation with β-Cyclodextrin - Chowdary, K.P.R.; Sambasiva Rao, A. (Asian Journal of Chemistry, 2010)
Aceclofenac, a widely prescribed non-steroidal antiinflammatory drug is practically insoluble in water and aqueous fluids, because of which it exhibits poor and variable dissolution rate and oral bioavailability. The objective of the study is to investigate the feasibility of using complexation with β-cyclodextrin (βCD) for enhancing the dissolution rate and bioavailability of aceclofenac. Aceclofenac-βCD inclusion complexes were prepared by kneading method and were evaluated for dissolution rate and bioavailability. The dissolution rate and bioavailability of aceclofenac were markedly enhanced by complexation with βCD. A 12.7 fold increase in the dissolution rate of aceclofenac was observed with aceclofenac-βCD (1:2) complex. Absorption rate was increased from 1.90 h-1 for aceclofenac to 2.76 and 4.33 h-1, respectively for βCD (1:1) and (1:2) complexes. (AUC)0-∝ was increased from 12.60 μgh/mL for aceclofenac to 42.51 and 49.20 μgh/mL for βCD (1:1) and (1:2) complexes, respectively.